Eastern tropical Pacific vegetation response to rapid climate change and sea level rise: A new pollen record from the Gulf of Tehuantepec, southern Mexico. (1st August 2016) - Hendy, I.L.; Minckley, T.A.; Whitlock, C.
Abstract: A 30, 000-year-long pollen record from the Gulf of Tehuantepec, southern Mexico shows the varying influence of air temperature, precipitation and eustatic sea-level rise on changes in coastal and upland vegetation patterns. During the late-glacial period, pine-juniper forests grew in the Sierra Madre del Sur along the Pacific Slope with broadleaf forests present at low elevations. Coastal wetland and riparian vegetation were limited in distribution. Significant cooling associated with Heinrich 1 (17, 000–15, 000 cal yr BP) resulted in an expansion of pine-juniper woodland. By the time of Bølling-Allerød warming (14, 700–13, 000 cal yr BP), extensive mangrove forest development was assisted by sea-level rise and reduced precipitation associated with a more southerly position of the Intertropical Convergence Zone (ITCZ) than at present. Concurrently, the expansion of oak into pine woodlands was promoted by warmer conditions than before. Increased summer precipitation in the early Holocene and stabilizing sea levels limited mangrove forests along the coast and allowed mixed conifer and hardwood forest to become more widespread inland. The onset of a more seasonal climate, driven by a weakening of the Mexican monsoon and a southerly shift in ITCZ position led to the establishment of modern open forests of pine and oak after 4300 cal yr BP. Highlights: Tropical forest composition responded to ITCZ-driven precipitation change during Heinrich 1, the Bølling-Allerød and Younger Dryas. The coolest interval of the last 30, 000 years occurred during Heinrich 1, while cooling during the Younger Dryas was minimal. Sea level rise and coastal geometry had a significant influence on the expansion of the mangrove forest ecosystem. Mangrove colonization kept pace with sea level rise, while ITCZ-driven precipitation changes were beneficial for mangroves. Holocene orbital forcing of precipitation also influenced the composition and canopy structure of Central American forests.